2014
DOI: 10.1016/j.ijbiomac.2014.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose and hyaluronic acid hybrid membranes: Production and characterization

Abstract: In this study, the effect of the addition of hyaluronic acid (HA) on bacterial cellulose (BC) production, under static conditions was evaluated in terms of the properties of the resulting BC hybrid membranes. HA was added to the fermentation process in three distinct time points: first day (BC-T0), third day (BC-T3) and sixth day (BC-T6). Analyses of FT-IR and CP/MAS (13)C NMR confirmed the presence of HA in bacterial cellulose membranes. The crystal structure, crystallinity index (Ic) surface roughness, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…These data are in agreement with those by Lopes et al [40], who suggested that hyaluronic acid (HA) added to the culture medium are retained inside the membrane. Therefore, during the BC synthesis, the free hydroxyl groups of the newly formed BC fibrils orientate toward the HA, becoming no longer available to occupy the surface, and lowering the surface hydrophilicity of the material.…”
Section: Resultssupporting
confidence: 93%
“…These data are in agreement with those by Lopes et al [40], who suggested that hyaluronic acid (HA) added to the culture medium are retained inside the membrane. Therefore, during the BC synthesis, the free hydroxyl groups of the newly formed BC fibrils orientate toward the HA, becoming no longer available to occupy the surface, and lowering the surface hydrophilicity of the material.…”
Section: Resultssupporting
confidence: 93%
“…Lopes et al (2014) analyzed the effect of hyaluronic acid (HA) during fermentation process. In conclusion, the authors observed a more hydrophilic behavior when the HA was included after six day of fermentation, indicating that the charged biopolymer adsorbs to the outer cellulose fibers, because the cellulose network was already formed.…”
Section: Static Contact Angle (Sca) Measurementsmentioning
confidence: 99%
“…FTIR investigated the chemical composition citrate and showed two characteristic forked absorption band at 3443 and 3379 cm −1 can be assigned to −NH 2 stretching vibration and another one absorption band at 3334, 3226 cm −1 related to tertiary amine (-CONH) stretching vibration [13,14] .…”
Section: Ftir-atr Analysismentioning
confidence: 99%